Peningkatan Kemampuan Kolaborasi dan Literasi Digital Melalui Penugasan E-Mind Mapping Berbantuan Google Slide - Baharudin Baharudin (Jurnal Didaktika Pendidikan Dasar, 2023)
Research is a Classroom Action Research that aims to improve students’ collaboration skills and digital literacy through e-mind mapping assisted by google slides in class IX students of Junior High School in social studies subjects. Increasing collaboration and digital literacy skills are essential to support 21st-century learning. Data collection uses observations and questionnaires to address as many as 28 students of class IX-A at State Junior Hight School 11 Kota Bima. The Observer will observe students' collaboration abilities, while students will fill out a questionnaire to determine the level of students’ digital literacy skills. Data analysis used quantitative data analysis in the form of the average results of each variable. The results showed an increase in the collaboration ability score from 79 in cycle 1 to 83 in cycle 2, the score category remained in the “High” category, and the Student's digital literacy skills also increased from 66 in cycle 1 to 72 in cycle 2, which was also accompanied by a change in indicators from “Enough” to “Good”.